Long-term response of an estuarine ecosystem to drastic nutrients changes in the Changjiang River during the last 59 years: A modeling perspective - Shi, Shenyang; Xu, Yi; Li, Weiqi; Ge, Jianzhong (Frontiers in Marine Science, 2022)
The riverine nutrient inputs to the ocean reflects land-use changes and can affect the health of coastal environments over time, especially for a highly-anthropogenically influenced river-estuary-shelf system. To investigate the impact of riverine inputs on the Changjiang Estuary ecosystem at a multi-decadal time scale where long-term observations are limited, we built a three-dimensional physics-biogeochemistry-coupled model system based on the Finite-Volume Community Ocean Model (FVCOM) and the European Regional Shelf Ecosystem Model (ERSEM). Our model successfully simulated the temporal and spatial nutrient variabilities in the river-estuary-shelf con7tinuum from 1960 to 2018. The results showed increasing trends of nitrate and phosphate and fluctuating silicate variability, thereby leading to rising nitrogen (N) to phosphorus (P) ratios and decreasing silicon (Si) to N and P ratios. Such changes in the stoichiometric relationship of nutrient species also alter the community structure of the primary producers in estuaries. Our model showed a general increase of diatoms over the 59 years, corresponding to decreased proportions of micro-phytoplankton and pico- phytoplankton. With different backgrounds of light and nutrient limitations in the river and inner shelf, our model suggests that the trend of the diatom proportion in the light-limited river mouth is more associated with silicate variability, with decreased diatom proportions occurring in the 2000s. Our model relates the hydroclimate, nutrient load, and biogeochemical cycling, reproducing estuarine ecosystem variability and clarifying issues such as the causality of the ecosystem interactions.